STUDY OF PLANS AND METHODS EXPERIMENTAL EVALUATION IN CONTROL PROBABILITIES OF FAILURE-FREE OPERATION AND COEFFICIENT READYNESS OF TECHNICAL SYSTEMS - Strelnikov , V. P.; Kiyashko , E. V.; Pyatetskaya , E. I. (Problems of Informatization and Management, 2021)
The main purpose of control tests is to confirm or refute the compliance of the reliability of technical systems with the requirements of the standard or technical specifications. The statement of the problem of planning control tests provides, as the initial data, the established values of the risks of the manufacturer (os) and the customer ((3), as well as the established values of the acceptance (Aa) and rejection (Ap) levels of the monitored reliability indicator.